Hydrogenation of cinnamaldehyde to hydrocinnamaldehyde over Pd nanoparticles deposited on nitrogen-doped mesoporous carbon - Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana V. (RSC Advances, 2016)
Palladium nanoparticles deposited on nitrogen-doped mesoporous carbon (NMC) were synthesized by simple ultrasonic-assisted method. This novel Pd-NMC catalyst was highly active and selective for the hydrogenation of cinnamaldehyde (CA) to hydrocinnamaldehyde (HCA) at room temperature (30 degrees C) under low H-2 pressure. The nitrogen-free mesoporous carbon (MC) and activated carbon (AC) were also employed as the support for Pd in the liquid-phase hydrogenation of CA. The incorporation of nitrogen into carbon matrix remarkably enhanced the catalytic activity and C=C bond hydrogenation selectivity (HCA selectivity of 93% with 100% CA conversion for Pd-NMC) in CA hydrogenation compared to the catalysts with no nitrogen (HCA selectivity of 66 and 47% for Pd-MC and Pd-AC, respectively). Moreover, Pd-NMC catalyst demonstrated an excellent recyclability without any loss in activity and HCA selectivity when it was reused for six times. The superior catalytic performance of Pd-NMC catalyst in CA hydrogenation is attributed to the small size of Pd nanoparticles due to presence of high nitrogen content (11.6 wt%) and mesoporous nature of NMC support.

Highly efficient and reusable Ru-NaY catalyst for the base free oxidation of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic acid - Kandasamy, Prabu; Gogoi, Pranjal; Venugopalan, Aswathy Thareparambil; Raja, Thirumalaiswamy (Catalysis Today, 2021)
Oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) is an important reaction for the production of recyclable bio-based polymers. Herein, we report a series of Ru nanoparticles supported on NaY zeolites catalysts for the oxidation of HMF to FDCA. The catalysts were prepared by simple ion exchanged method. Among all the catalysts, the optimized 3 wt % Ru-NaY catalyst showed superior catalytic activity under base free conditions with a shorter period of reaction time. The conversion of HMF was 100 % with 94 % FDCA yield. This catalyst was reused for fourth cycles, with an insignificant decrease in the yield of FDCA. H2-chemisorption and HRTEM studies confirmed that high metal dispersion and small size of Ru nanoparticles play vital roles for the HMF oxidation. In addition, the acidic hydroxyl groups of the supercage as well as higher amount of metallic Ru° are also responsible for the high yield and productivity of FDCA.